Visions in the Ville: Looking toward the next 125 years. Volume 2: Design proposals - Belanger, Blake; Hahn, Howard D. (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2014)
The 2014 “Visions in the Ville” summer studio explored Aggieville’s potential as the community looks toward the future. The studio spanned eight weeks and was offered by the Department of Landscape Architecture and Regional & Community Planning at Kansas State University. Associate Professors Blake Belanger and Howard Hahn directed the efforts of fourteen mid-level graduate landscape architecture students, and documented the studio’s research and design findings in two volumes: Volume 1: Critical Mapping and Volume 2: Design Proposals. The intent of the studio was to identify ideas, visions, and strategies that will contribute to a community dialogue about enhancing Aggieville’s future. The studio researched the history, character, economics, demographics, and ecological conditions of Aggieville, as well as the district’s broader role in the evolving community and regional context. Volume 2 builds on the studio’s research and strategies developed through critical mapping, and presents five planning and design proposals for Aggieville and its context. Students repeatedly engaged community stakeholders to discuss design development and presented their final ideas in various venues, including a public open house, a presentation to the Manhattan City Commission, and a public exhibit at “Aggieville’s 125th Birthday Street Fair and Dance.” Primary findings include design proposals for improving physical connectivity and partnerships across the community, providing medium to high-density mixed-use urban infill, developing permanent and temporary regional attractions, and enhancing civic space in and around Aggieville.
Keywords: Kansas State University; Aggieville, Manhattan; Landscape architecture; Urban design; Community planning